1997
DOI: 10.1074/jbc.272.32.20205
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Template-Primers Containing Propanodeoxyguanosine by DNA Polymerase β

Abstract: Propanodeoxyguanosine (PdG) is a model for several unstable exocyclic adducts formed by reaction of DNA with bifunctional carbonyl compounds generated by lipid peroxidation. The effect of PdG on DNA synthesis by human DNA polymerase ␤ was evaluated using template-primers containing PdG at defined sites. DNA synthesis was conducted in vitro and the products were analyzed by polyacrylamide gel electrophoresis and DNA sequencing. The extent of PdG bypass was low and the products comprised a mixture of base pair s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…M 1 dG adducts, produced during lipid peroxidation, seem to be repaired by NER in both bacteria and human cells (23). Like other adducts, such as CPDs, which arrest RNAPs and are repaired by TCR, PdG, the stable analog of M 1 dG, also inhibits replication by DNA polymerases (27,28,37). Therefore, it was reasoned that M 1 dG or PdG in the transcribed strand of active genes might impede translocation by RNAPs and potentially initiate TCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M 1 dG adducts, produced during lipid peroxidation, seem to be repaired by NER in both bacteria and human cells (23). Like other adducts, such as CPDs, which arrest RNAPs and are repaired by TCR, PdG, the stable analog of M 1 dG, also inhibits replication by DNA polymerases (27,28,37). Therefore, it was reasoned that M 1 dG or PdG in the transcribed strand of active genes might impede translocation by RNAPs and potentially initiate TCR.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of frameshift mutations by PdG and M 1 dG suggests that the adducts alter DNA polymerase elongation (19,20,22). PdG does, in fact, interfere with nucleotide insertion and translocation by Klenow fragment and DNA polymerase ␤ in vitro (27,28); therefore, it is possible that MDA adducts may also impede RNA polymerases. If so, M 1 dG in expressed genes might be recognized and removed by TCR.…”
mentioning
confidence: 99%
“…3) and the lack of a further increase in rate with increasing run length suggests the involvement of additional mechanisms and/or unusual interactions of Pol with its substrates. Possibilities include misalignment in the polymerase active site (35)(36)(37)(38)(39), nucleotide misinsertion followed by primer relocation (32,40), or some other mechanism. The fact that the relationship between single-base deletion rates and homopolymeric run length are different for Pol compared with Pol ␤ (Fig.…”
Section: Fidelity Of Dna Polymerasementioning
confidence: 99%
“…NMR spectroscopy of the PdGadducted oligodeoxynucleotides has revealed that when placed opposite dC, PdG adopts a syn orientation within the duplex and introduces a localized structural perturbation that is pHand sequence-dependent (9,10). The inability of PdG to form normal Watson-Crick hydrogen bonds severely blocks DNA synthesis both in vitro (11,12) and in vivo (13)(14)(15)(16), and the replication that does occur results in mutations (13)(14)(15)(16). Specifically, PdG-induced base substitutions occurred at an overall frequency of 7.8 ϫ 10 Ϫ2 and 7.5 ϫ 10 Ϫ2 /translesion synthesis in the COS-7 (14) and in the nucleotide excision repair-deficient human cells (16), respectively.…”
mentioning
confidence: 99%